1997
DOI: 10.1007/s004200050168
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cognitive bias on the perceived odor, irritation and health symptoms from chemical exposure

Abstract: The results provide strong evidence that both the perceived odor and cognitive expectations about a chemical can significantly affect how individuals respond to it. Moreover, because naive control subjects appear to exhibit extreme variation in their cognitive evaluations of chemical effects, there may be limited value in using non-exposed controls to assess the irritancy of chemicals for worker populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 36 publications
11
79
0
1
Order By: Relevance
“…Our postchallenge quantitative measurement of olfactory thresholds did not reveal Scand J Work Environ Health 1998, "0124, no 5 any aberration in olfactory function that could explain the reaction differences. Thus our results are in accordance with the findings of both cacosmia and normal olfactory function after long-term exposure to solvents (5,26).…”
Section: Discussionsupporting
confidence: 92%
“…Our postchallenge quantitative measurement of olfactory thresholds did not reveal Scand J Work Environ Health 1998, "0124, no 5 any aberration in olfactory function that could explain the reaction differences. Thus our results are in accordance with the findings of both cacosmia and normal olfactory function after long-term exposure to solvents (5,26).…”
Section: Discussionsupporting
confidence: 92%
“…Dalton and colleagues (Dalton 1999;Dalton et al 1997) demonstrated that inducing beliefs about harmful consequences of exposure to certain odorants resulted not only in increased intensity but also in irritancy of those odorants as well as enhanced frequency and intensity of symptom reports. These findings led Dalton to propose that changes in health effects and symptom reporting are modulated by changes in odor perception (Dalton 2002(Dalton , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Dalton and colleagues, for example, evaluated whether information about the health consequences of exposure to acetone would alter the ratings of odor and irritation during exposure and/or the frequency of reported health symptoms following exposure. 225 Ninety subjects were exposed for 20 minutes to 200 ppm of phenyl ethyl alcohol (PEA; a relatively nonirritating rose-like smelling agent) and to 800 ppm acetone, an agent with more irritating properties. Subjects were assigned to three groups: the positive bias group was told they would be exposed to natural extracts that were commonly used in aromatherapy and may have beneficial effects on mood and health; the negative bias group was told they would be exposed to industrial solvents that purportedly caused health effects and cognitive problems following long-term exposure; and the neutral bias group was told they would be exposed to standard odorants commonly used and approved for olfactory research.…”
Section: B Subject Characteristics I Smoking Behaviormentioning
confidence: 99%